2020
DOI: 10.1002/htj.21709
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent modeling of rheological and thermophysical properties of nanoencapsulated PCM slurry

Abstract: Nanoencapsulated phase change material slurries (NPCMS) combine properties of carried fluid and phase change material (PCM). Usage of NPCMS instead of water as a working fluid has a lot of advantages in many industrial fields. The costly and time-consuming determination of thermophysical properties of NPCMS through the experimental analysis led the current investigations to use soft computing methods like correlating, artificial neural network (ANN), and ant colony optimization (ACO R ). In this study, the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, the advantages of PCMS have made it a growing topic in different areas and several empirical correlations are proposed to calculate its characteristic properties. In this regard, Jirandeh et al [15] presented an empirical correlation for NPCMS using artificial neural networks and colony optimization. The model is derived by investigating AP-25 particles surrounded by a Styrene shell in Newtonian fluid flow conditions within the test region.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…However, the advantages of PCMS have made it a growing topic in different areas and several empirical correlations are proposed to calculate its characteristic properties. In this regard, Jirandeh et al [15] presented an empirical correlation for NPCMS using artificial neural networks and colony optimization. The model is derived by investigating AP-25 particles surrounded by a Styrene shell in Newtonian fluid flow conditions within the test region.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Various ways of increasing their thermal conductivity have been tested, including the direct addition of materials with a high thermal conductivity (e.g., metal particles) to PCMs [9]; the use of additional ribbing to increase the heat exchange surface [10]; placing the PCM in a porous conductive structure [11,12] or metallic foams [9,13]; and encapsulation-collecting PCMs in a large number of small shells. The encapsulation of the PCM allows for the initiation of the phase change simultaneously Energies 2023, 16, 6926 2 of 14 in all washed containers. Encapsulation techniques can be divided into macro-, micro-, and nanoencapsulation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulation techniques can be divided into macro-, micro-, and nanoencapsulation [14,15]. Microencapsulation is a process in which PCM particles (with a diameter of about 0.1-1000 µm) are covered with a thin layer of a natural or synthetic polymer with a thickness of several micro-or even nanometers [16][17][18]. In consequence, the encapsulated PCM is used as a passive heat energy storage in building materials, filling building spaces for cooling and heating rooms, as an additive in textiles, among others [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In AI based models, some of the properties of PCM and nano particle are used to predict some of the thermophysical properties of NEPCM [27]. The NEPCMs are classified as nano fluid in most of the literature however these materials experience a phase change process and are not utilized in liquid phase only.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is many AI based models for nanofluid but they are not valid for NEPCMs and just few studies can be found in the literature for modeling of NEPCM by AI models. For instance, artificial neural network which is the base of AI is used to predict the thermal conductivity and viscosity of nano encapsulated PCM slurry [27]. They used temperature of the NEPCM and the nano particle concentration as the predictor in their model.…”
Section: Introductionmentioning
confidence: 99%